Composite lithium supplement material and preparation method thereof, positive pole piece and battery
By distributing organolithium compounds in the pores of the porous carbon matrix to form composite lithium supplement materials, the problem of low battery capacity of organolithium compound lithium supplement agents is solved, and efficient lithium supplementation effect and electrochemical performance improvement are achieved.
Patent Information
- Application Number
- CN202411550482.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-02-28
AI Technical Summary
When organolithium compounds are used as lithium supplement agents, the battery capacity is low and the decomposition voltage is high, resulting in low utilization and poor electrochemical performance.
The porous carbon matrix is used as the dispersion medium to distribute the organolithium compound in its pores to form a composite lithium supplement material. By controlling the pore capacity and average pore size of the porous carbon matrix, the decomposition voltage is reduced, and the utilization rate and positive electrode capacity of the lithium supplement agent are improved.
It significantly improves the conductivity of lithium supplement agents, reduces the decomposition voltage, enhances the cathode capacity and the electrochemical performance of the battery, and is suitable for large-scale production.
Smart Images

Figure CN119542421A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of batteries, and in particular relates to a composite lithium supplement material and a preparation method thereof, as well as a positive electrode sheet and a battery. Background Art
[0002] During the formation and charge-discharge cycle of lithium-ion batteries, SEI film is usually continuously formed on the surface of the negative electrode, which consumes the active lithium in the battery and causes irreversible loss of battery capacity. This phenomenon is particularly significant in electrochemical systems with low initial coulombic efficiency of negative electrode materials, such as LFP-Graphite (lithium iron phosphate-graphite system) and negative electrode silicon-containing systems. In response to this phenomenon, lithium replenishment technology has received more and more attention. It is generally believed that lithium replenishment can not only make up for the difference in initial efficiency between positive and negative electrodes and increase battery capacity, but also improve battery cycle by pre-storing some active lithium. Common lithium replenishment technologies include negative electrode lithium replenishment and positive electrode lithium replenishment. Negative electrode lithium replenishment generally uses metallic lithium (lithium powder, lithium foil) as a lithium source. Negative electrode lithium replenishment has the advantage of high capacity, but has strict requirements for manufacturing process and operating environment, and is accompanied by safety hazards, which is not conducive to large-scale production. Positive electrode lithium replenishment is highly compatible with existing battery processes and has no safety hazards. It has been applied in small batches.
[0003] There are three common positive electrode lithium supplement materials: 1) The first category is binary lithium-containing compounds, such as Li2O2, Li3N and Li2S. 2) The second category is lithium-rich compounds, such as LFO (Li5FeO4) and LNO (Li2NiO2); 3) The third category is organic lithium compounds, including Li2C4O4, Li2C2O4, Li2C3O5, Li2C5O5, Li2C4O6 and Li2C6O6.
[0004] As for the third type of organic lithium compound lithium supplement materials, this type of substance can exist stably in the air, but when applied to the positive electrode system, the positive electrode capacity is relatively low and needs to be improved. Summary of the invention
[0005] The present invention aims to solve the problem of low battery capacity when organic lithium compounds are used as lithium supplement agents, at least to a certain extent. To this end, one object of the present invention is to provide a composite lithium supplement material and a preparation method thereof, as well as a positive electrode plate and a battery. The positive electrode organic lithium supplement material has a low decomposition voltage, which is conducive to increasing the positive electrode capacity and improving the electrochemical performance of the battery.
[0006] The first aspect of the present application provides a composite lithium supplement material. According to an embodiment of the present invention, the composite lithium supplement material comprises: a porous carbon matrix, and an organic lithium compound distributed at least in the pores of the porous carbon matrix; the pore volume of the porous carbon matrix is 0.4 cm 3 / g~1.2cm 3 / g, and the average pore size of the porous carbon matrix is 5nm~70nm.
[0007] The composite lithium supplement material of the present application uses an organic lithium compound as a lithium supplement agent (i.e., a lithium supplement active component), which is beneficial to reducing the decomposition voltage, and uses a porous carbon matrix as a good dispersion medium, which alleviates the agglomeration problem of conventional nanomaterials, helps to improve the utilization rate of the lithium supplement agent, increases the positive electrode capacity, and facilitates the processing of the positive electrode slurry in the later stage. At the same time, the structure of the organic lithium compound lithium supplement agent wrapped in a porous carbon matrix can provide a good conductive network, significantly improve the conductivity of the lithium supplement agent, reduce the decomposition potential of the lithium supplement agent, and improve the utilization rate of the lithium supplement agent. The present application further improves the lithium supplement effect and the positive electrode capacity by controlling the pore volume and average pore size of the porous carbon matrix.
[0008] According to an embodiment of the present invention, the above-mentioned composite lithium supplement material may further include at least one of the following additional technical features:
[0009] In some embodiments, the porous carbon matrix includes at least one of graphite, soft carbon and hard carbon; and / or the organic lithium compound includes at least one of Li2C4O4, Li2C2O4, Li2C3O5, Li2C5O5, Li2C4O6 and Li2C6O6.
[0010] In some embodiments, the mass ratio of the porous carbon matrix to the organic lithium compound is 5:1 to 1:5.
[0011] In some embodiments, the crystal size of the organolithium compound is 1 nm to 20 nm.
[0012] The second aspect of the present application provides a method for preparing a composite lithium supplement material, comprising: distributing an organic lithium compound in the pores of a porous carbon matrix to obtain a composite lithium supplement material; in the composite lithium supplement material, the pore volume of the porous carbon matrix is 0.4 cm 3 / g~1.2cm 3 / g, and the average pore size of the porous carbon matrix is 5nm~70nm.
[0013] The preparation method provided in the present application utilizes the confinement effect of a porous carbon matrix to prepare a nano-scale lithium supplement, which has the beneficial effects of good dispersion performance, low agglomeration, and high conductivity; and the preparation method is simple, easy to operate, and is conducive to large-scale production.
[0014] In some embodiments, the method of distributing the organolithium compound within the pores of the porous carbon matrix comprises a recrystallization method.
[0015] In some embodiments, the recrystallization method includes the steps of: adding a porous carbon matrix and an organic lithium compound to a first solvent to obtain a mixed solution; adding a second solvent to the mixed solution for recrystallization treatment; removing the first solvent and the second solvent to obtain a composite lithium supplement material; the solubility of the organic lithium compound in the second solvent is lower than that in the first solvent.
[0016] In some embodiments, each raw material satisfies at least one of the following (1) to (4):
[0017] (1) The porous carbon matrix includes at least one of graphite, soft carbon and hard carbon;
[0018] (2) The organic lithium compound includes at least one of Li2C4O4, Li2C2O4, Li2C3O5, Li2C5O5, Li2C4O6 and Li2C6O6;
[0019] (3) the first solvent includes water or other solvents having high solubility for the organolithium compound;
[0020] (4) The second solvent includes a solvent such as ethanol which has a low solubility in the organolithium compound.
[0021] In some embodiments, in the step of adding the second solvent to the mixed solution for recrystallization, the control parameters include: a stirring speed of 100 rpm to 5000 rpm; and / or an addition speed of the second solvent of 0.5 ml / min to 20 ml / min.
[0022] In some embodiments, the method further includes the step of preparing a porous carbon matrix: subjecting a porous carbon precursor to an activation treatment to obtain a porous carbon matrix; the carbon precursor includes at least one of biomass and resin; and the activation treatment includes chemical activation or physical activation.
[0023] The third aspect of the present application provides a positive electrode plate, comprising the above-mentioned composite lithium-replenishing material, or comprising the composite lithium-replenishing material obtained by the above-mentioned preparation method.
[0024] The positive electrode plate provided in the present application is made of a composite lithium replenishing material, which exhibits a good lithium replenishing effect and is applied to batteries to help increase the positive electrode capacity.
[0025] In some embodiments, the positive electrode plate includes a current collector layer and an active material layer, the active material layer contains a composite lithium supplement material; the mass percentage of the composite lithium supplement material in the active material layer is 0.5% to 10%.
[0026] The third aspect of the present application provides a battery, comprising the above-mentioned positive electrode plate; or, comprising the above-mentioned composite lithium-supplementing material; or, comprising the composite lithium-supplementing material obtained by the above-mentioned preparation method.
[0027] The battery provided in this application exhibits good electrochemical performance.
[0028] A fourth aspect of the present application provides an electrical device comprising the above-mentioned battery.
[0029] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0031] Figure 1 This is a SEM image of the composite lithium supplement material provided in Example 1 of the present application.
[0032] Figure 2 yes Figure 1 The enlarged view of the part shown in the center line box.
[0033] Figure 3 This is a SEM image of the lithium supplement material provided in Comparative Example 1 of the present application.
[0034] Figure 4 yes Figure 3 The enlarged view of the part shown in the center line box represents lithium oxalate (Li2C2O4) aggregates. DETAILED DESCRIPTION
[0035] The embodiments of the present invention are described in detail below. The embodiments described below are exemplary and are only used to explain the present invention, and should not be understood as limiting the present invention.
[0036] It should be noted that the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. Further, in the description of the present invention, unless otherwise specified, the meaning of "plurality" is two or more.
[0037] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0038] In this document, the terms “include” or “comprising” are open expressions, that is, including the contents specified in the present invention but not excluding other contents.
[0039] As used herein, the terms "optionally", "optional" or "optionally" generally mean that the subsequently described event or circumstance may but need not occur, and that the description includes instances where the event or circumstance occurs and instances where it does not.
[0040] The scheme of the present invention will be explained below in conjunction with the embodiments. It will be appreciated by those skilled in the art that the following embodiments are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. Where specific techniques or conditions are not indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used are not indicated by the manufacturer and are all conventional products that can be obtained commercially.
[0041] The first aspect of the embodiment of the present application provides a composite lithium supplement material, which comprises: a porous carbon matrix, and an organic lithium compound at least distributed in the pores of the porous carbon matrix; the pore volume of the porous carbon matrix is 0.4 cm 3 / g~1.2cm 3 / g, the average pore size of the porous carbon matrix is 5nm to 70nm, and the grain size of the organic lithium compound is 1nm to 20nm. In a specific example, the pore volume of the porous carbon matrix is 0.4cm 3 / g, 0.5cm 3 / g, 0.6cm 3 / g, 0.7cm 3 / g, 0.8cm 3 / g, 0.9cm 3 / g, 1.0cm 3 / g, 1.1cm 3 / g or 1.2cm 3 / g, etc.; in a specific example, the average pore size of the porous carbon matrix is 5nm, 10nm, 15nm, 20nm, 25nm, 30nm, 35nm, 40nm, 45nm, 50nm, 55nm, 60nm, 65nm or 70nm, etc.
[0042] As lithium supplement materials, inorganic lithium compounds (such as Li2O2, Li3N or Li2S, etc.) have the advantage of low decomposition voltage, but have the disadvantage of poor stability, easy to react with air and water, easy to produce gas, affecting the safety performance of the battery, and leading to high requirements for the manufacturing process and operating environment of electrodes and batteries, which is not conducive to mass production. Organic lithium compounds are highly stable and can exist stably in the air. Their disadvantages are that the decomposition voltage is generally high (≥4.5V), not easy to decompose, and low utilization rate; and the operating voltage of the battery is lower than the decomposition voltage of inorganic lithium compounds. Therefore, inorganic lithium compounds are incompatible with batteries, which is not conducive to improving the positive electrode capacity.
[0043] In order to solve the problem of high decomposition voltage of organic lithium compounds, the conventional technical concept is to reduce the decomposition voltage by optimizing the morphology and particle size (nano-crystallization). In theory, this concept can increase the reactive sites and reduce the decomposition overpotential, but conventional nano-crystallized particles are prone to agglomeration, which reduces the contact area with the electrolyte, reduces the lithium replenishment efficiency, and easily leads to increased battery polarization, reducing the cycle stability and capacity of the battery; at the same time, it is easy to cause gelation risk in the later preparation of positive electrode slurry.
[0044] The composite lithium supplement material provided by the present application uses an organic lithium compound as a lithium supplement agent (i.e., a lithium supplement active component), uses a nanoscale lithium supplement agent, is conducive to reducing the decomposition voltage, and uses a porous carbon matrix as a good dispersion medium, which alleviates the agglomeration problem of conventional nanomaterials, is conducive to improving the utilization rate of the lithium supplement agent, and is convenient for the processing of the later positive electrode slurry. At the same time, the organic lithium compound is distributed in the pores of the porous carbon matrix, forming a structure similar to the porous carbon matrix encapsulating the organic lithium compound lithium supplement agent, which can provide a good conductive network, significantly improve the conductivity of the lithium supplement agent, and reduce the decomposition potential of the lithium supplement agent.
[0045] In the embodiment of the present application, by reasonably setting the average pore size and pore volume parameter range of the porous carbon matrix, it is beneficial to improve the lithium supplement effect and improve the electrochemical performance of the battery. The pore size and pore volume of the porous carbon matrix have a great influence on the deposition of the lithium supplement active component. 1) Considering from the perspective of average pore size: adopting a porous carbon matrix with an appropriate average pore size, on the one hand, it is beneficial to give full play to the confinement effect of the pore size, synthesize organic lithium compounds with smaller crystal particle size, and reduce the decomposition voltage; on the other hand, it ensures that the lithium supplement active component is fully diffused into the pores of the porous carbon matrix in the form of ions, and ensures that the lithium supplement active component is recrystallized and deposited in the pores, rather than deposited on the surface of the porous carbon matrix, thereby facilitating the improvement of the utilization rate, conductivity and positive electrode gram capacity of the composite lithium supplement material. 2) Considering from the perspective of pore volume: adopting a porous carbon matrix with an appropriate pore volume, on the one hand, it is beneficial to reduce the damage of the conductive path inside the porous carbon matrix and improve the conductivity; on the other hand, it is beneficial to ensure that the lithium supplement active component is recrystallized and deposited inside the pore as much as possible rather than deposited on the surface, thereby improving the decomposition efficiency and utilization rate of the lithium supplement active component.
[0046] Furthermore, the pore volume of the porous carbon matrix is 0.6 cm 3 / g~1.0cm 3 / g, and the average pore size of the porous carbon matrix is 10nm to 30nm. In a specific example, the average pore size of the porous carbon matrix is 10nm, 12nm, 14nm, 16nm, 18nm, 20nm, 22nm, 24nm, 26nm, 28nm or 30nm.
[0047] In some embodiments, the porous carbon matrix includes at least one of graphite, soft carbon and hard carbon; and / or the organic lithium compound includes at least one of Li2C4O4, Li2C2O4, Li2C3O5, Li2C5O5, Li2C4O6 and Li2C6O6.
[0048] The embodiment of the present application adopts a porous carbon matrix material including at least one of graphite, soft carbon and hard carbon, which has a stable structure, uniform internal pore distribution, a large specific surface area, and good conductivity. It can give full play to the effects of confinement, dispersion and conductive network, and improve the electrochemical properties of the composite lithium supplement material.
[0049] This embodiment uses an organic lithium compound including at least one of Li2C4O4, Li2C2O4, Li2C3O5, Li2C5O5, Li2C4O6 and Li2C6O6 as a lithium supplement agent, which exhibits higher stability and safety than inorganic lithium compounds. This application further reduces the decomposition voltage by providing nano-scale lithium supplement particles with higher dispersibility, so that the composite lithium supplement material exhibits a good lithium supplement effect, which is conducive to mass production.
[0050] In some embodiments, the mass ratio of the porous carbon matrix to the organic lithium compound is 5:1 to 1:5. In specific examples, the mass ratio of the porous carbon matrix to the organic lithium compound is 5:1, 4:1, 3:1, 2:1, 1:1, 1:2, 1:3, 1:4 or 1:5, etc.
[0051] Furthermore, the mass ratio of the porous carbon matrix to the organic lithium compound is 3:1 to 1:3.
[0052] The embodiment of the present application further sets the mass ratio of the porous carbon matrix and the organic lithium compound, which is beneficial to further provide the lithium replenishment performance of the composite lithium replenishment material and improve the electrochemical performance of the battery.
[0053] In some embodiments, the crystal size of the organolithium compound is 1 nm to 20 nm.
[0054] In the embodiment of the present application, the organic lithium compound crystal size formed by the confinement effect of the porous carbon matrix meets the above conditions, which is beneficial to reduce the decomposition voltage, improve the utilization rate of the composite lithium supplement material, increase the positive electrode capacity, and improve the electrochemical performance of the battery.
[0055] Furthermore, the crystal size of the organic lithium compound is 2 nm to 10 nm. In a specific example, the crystal size of the organic lithium compound is 2 nm, 3 nm, 4 nm, 5 nm, 6 nm, 7 nm, 8 nm, 9 nm, 10 nm, etc.
[0056] A second aspect of the present application provides a method for preparing a composite lithium supplement material, comprising:
[0057] The organic lithium compound is distributed in the pores of the porous carbon matrix to obtain a composite lithium supplement material; in the composite lithium supplement material, the pore volume of the porous carbon matrix is 0.4 cm 3 / g~1.2cm 3 / g, the average pore size of the porous carbon matrix is 5nm to 70nm. In a specific example, the pore volume of the porous carbon matrix is 0.4cm 3 / g, 0.5cm 3 / g, 0.6cm 3 / g, 0.7cm 3 / g, 0.8cm 3 / g, 0.9cm 3 / g, 1.0cm 3 / g, 1.1cm 3 / g or 1.2cm 3 / g, etc.; in a specific example, the average pore size of the porous carbon matrix is 5nm, 10nm, 15nm, 20nm, 25nm, 30nm, 35nm, 40nm, 45nm, 50nm, 55nm, 60nm, 65nm or 70nm, etc.
[0058] The preparation method provided in the embodiment of the present application utilizes the confinement effect of the porous carbon matrix to prepare a nano-scale lithium supplement, which has the beneficial effects of good dispersion performance, low agglomeration and high conductivity.
[0059] Furthermore, the pore volume of the porous carbon matrix is 0.6 cm 3 / g~1.0cm 3 / g, and the average pore size of the porous carbon matrix is 10nm to 30nm. In a specific example, the average pore size of the porous carbon matrix is 10nm, 12nm, 14nm, 16nm, 18nm, 20nm, 22nm, 24nm, 26nm, 28nm or 30nm.
[0060] The embodiments of the present application provide for further designing the pore volume and average pore size of the porous carbon matrix, which is beneficial to further reduce the decomposition voltage, improve the utilization rate of lithium supplement materials, increase the positive electrode capacity, and improve the electrochemical performance of the battery.
[0061] In some embodiments, the crystal size of the organolithium compound is 1 nm to 20 nm.
[0062] In the embodiment of the present application, the organic lithium compound crystal size formed by the confinement effect of the porous carbon matrix meets the above conditions, which is beneficial to reduce the decomposition voltage, improve the utilization rate of the composite lithium supplement material, increase the positive electrode capacity, and improve the electrochemical performance of the battery.
[0063] Furthermore, the crystal size of the organic lithium compound is 2 nm to 10 nm. In a specific example, the crystal size of the organic lithium compound is 2 nm, 3 nm, 4 nm, 5 nm, 6 nm, 7 nm, 8 nm, 9 nm, 10 nm, etc.
[0064] In some embodiments, in the obtained composite lithium supplement material, the mass ratio of the porous carbon matrix to the organic lithium compound is 5:1 to 1:5. In specific examples, the mass ratio of the porous carbon matrix to the organic lithium compound is 5:1, 4:1, 3:1, 2:1, 1:1, 1:2, 1:3, 1:4 or 1:5, etc.
[0065] In some embodiments, the method of distributing the organolithium compound within the pores of the porous carbon matrix comprises a recrystallization method.
[0066] In order to solve the problem of high decomposition voltage of organic lithium compounds, the prior art also adopts the technical concept of carbon coating organic lithium compounds by vapor deposition to improve the conductivity of the material and reduce the decomposition voltage. However, the commonly used carbon sources in the vapor deposition process include ethanol, methanol, toluene, methane, ethylene and acetylene. The main problem of this idea is that the cracking temperature of conventional carbon sources is basically above 600°C, while organic lithium compounds basically decompose at 400°C to 500°C. The conventional carbon coating idea cannot solve this problem.
[0067] The preparation method provided in the embodiment of the present application adopts a recrystallization method, does not require high-temperature treatment, and does not have the problem of carbon source decomposition. A composite lithium-supplementing material in which a lithium-supplementing agent is loaded in the pores of a porous carbon matrix can be prepared. On the one hand, it provides a dispersion medium for the nano-lithium-supplementing agent, and on the other hand, it improves the electrical conductivity, thereby reducing the decomposition voltage.
[0068] The recrystallization reaction adopted in the embodiment of the present application is a loss-free reaction. Therefore, in the raw materials of the preparation method, the mass ratio of the porous carbon matrix and the organic lithium compound used is equal to, or nearly equal to, the mass ratio of the porous carbon matrix and the organic lithium compound in the obtained product (due to conventional detection errors or operational errors and other experimental reasons, the mass ratio of the porous carbon matrix and the organic lithium compound in the raw materials may be not exactly the same as the mass ratio of the porous carbon matrix and the organic lithium compound in the obtained product).
[0069] In some embodiments, the pores in the porous carbon matrix are a continuously interconnected pore structure, including interconnections between pores and interconnections between the pores and the external environment.
[0070] The pores are connected to the external environment, which is beneficial for the ions of the organic lithium compound dissolved in the first solvent to enter the pores; the interconnected pores are beneficial for the recrystallization of the organic lithium compound, ensuring the continuous and uniform growth of the crystals, and growing into crystal particles of appropriate grain size under the limiting effect of the pore diameter.
[0071] In some embodiments, the recrystallization method comprises the steps of:
[0072] adding a porous carbon matrix and an organic lithium compound into a first solvent to obtain a mixed solution;
[0073] adding a second solvent to the mixed solution for recrystallization;
[0074] Performing a treatment to remove the first solvent and the second solvent to obtain a composite lithium supplement material;
[0075] The solubility of the organolithium compound in the second solvent is lower than that in the first solvent.
[0076] The embodiment of the present application utilizes the different solubility of the organolithium compound in two solvents to achieve recrystallization. By selecting an appropriate solvent combination, the solubility of the target compound can be more accurately controlled, thereby achieving more efficient separation and purification; and it can be carried out at room temperature, with less energy consumption. The cost is low, the operation is convenient, and it is conducive to large-scale expansion.
[0077] Furthermore, the first solvent is a good solvent, and the second solvent is a poor solvent.
[0078] That is, the organic lithium compound has a higher solubility in the first solvent and a lower solubility in the second solvent; after the second solvent is added, the organic lithium compound will gradually precipitate due to its lower solubility in the second solvent, thereby achieving recrystallization.
[0079] Further, the dissolution of the organic lithium compound in the first solvent reaches a saturated state.
[0080] The dissolution of the organic lithium compound in the first solvent reaches a saturated state, which facilitates efficient recrystallization in the later stage.
[0081] Furthermore, in the process of preparing the mixed solution, the porous carbon matrix can be first dispersed in the first solvent and then the organic lithium compound can be dissolved in the first solvent; the organic lithium compound can be first dissolved in the first solvent and then the porous carbon matrix can be added for dispersion; or the porous carbon matrix and the organic lithium compound can be added to the first solvent at the same time, and the porous carbon matrix can be dispersed in the solution of the organic lithium compound by mixing.
[0082] Furthermore, the step of removing the first solvent and the second solvent may be performed by a drying process, specifically, vacuum drying, spray drying, and the like.
[0083] In the embodiment of the present application, spray drying is used to effectively remove the first solvent and the second solvent to obtain a lithium-supplemented composite material.
[0084] In some embodiments, each raw material satisfies at least one of the following (1) to (4):
[0085] (1) The porous carbon matrix includes at least one of activated carbon, porous carbon fiber, graphene and carbon nanotubes;
[0086] (2) The organic lithium compound includes at least one of Li2C4O4, Li2C2O4, Li2C3O5, Li2C5O5, Li2C4O6 and Li2C6O6;
[0087] (3) the first solvent includes water or other solvents having high solubility for the organic lithium salt;
[0088] (4) The second solvent includes a solvent such as ethanol that has a low solubility in the organic lithium salt.
[0089] The embodiment of the present application adopts a porous carbon matrix material including at least one of graphite carbon, soft carbon and hard carbon, which has a stable structure, uniform internal pore distribution, large specific surface area, and good conductivity. It can give full play to the effects of confinement, dispersion and conductive network, and improve the electrochemical properties of the composite lithium supplement material.
[0090] This embodiment uses an organic lithium compound including at least one of Li2C4O4, Li2C2O4, Li2C3O5, Li2C5O5, Li2C4O6 and Li2C6O6 as a lithium supplement agent, which exhibits higher stability and safety than inorganic lithium compounds. This application further reduces the decomposition voltage by providing nano-scale lithium supplement particles with higher dispersibility, so that the composite lithium supplement material exhibits a good lithium supplement effect, which is conducive to mass production.
[0091] The embodiment of the present application uses a solvent including water as the first solvent and a solvent including ethanol as the second solvent, which is low in cost, safe and environmentally friendly, and facilitates the control of the crystallization process.
[0092] In some embodiments, in the step of adding the second solvent to the mixed solution for recrystallization, the control parameters include:
[0093] The stirring speed is: 100 rpm to 5000 rpm; and / or the adding speed of the second solvent is 0.5 ml / min to 20 ml / min.
[0094] In the process of adding the second solvent for recrystallization, the stirring speed is reasonably controlled to facilitate the full mixing of the organic lithium compound, the first solvent and the second solvent, promote crystal growth, and recrystallize to form uniform grains of target size.
[0095] By properly controlling the adding speed and stirring speed of the second solvent, uniform recrystallization is ensured in the pores of the porous carbon matrix to form a grain structure with regular morphology and appropriate size.
[0096] In a specific example, the stirring speed is 100rpm, 200rpm, 300rpm, 400rpm, 500rpm, 600rpm, 700rpm, 800rpm, 850rpm, 900rpm, 950rpm, 1000rpm, 1050rpm, 1100rpm, 1150rpm, 1200rpm, 1250rpm, 1300rpm, 1350rpm, 1400rpm, 1450rpm, 1500rpm, 1600rpm, 1700rpm, 1800rpm, 1900rpm, 2000rpm, 2500rpm, 3000rpm, 3500rpm, 4000rpm, 4500rpm, 5000rpm, etc. In a specific example, the addition rate of the second solvent is 0.5ml / min, 1ml / min, 2ml / min, 2.5ml / min, 3ml / min, 3.5ml / min, 4ml / min, 4.5ml / min, 5ml / min, 5.5ml / min, 6ml / min, 6.5ml / min, 7ml / min, 7.5ml / min, 8ml / min, 8.5ml / min, 9ml / min, 9.5ml / min, 10ml / min, 12ml / min, 14ml / min, 16ml / min, 18ml / min, 20ml / min and the like.
[0097] In some embodiments, the method further comprises the step of preparing a porous carbon matrix: subjecting a porous carbon precursor to an activation treatment to obtain a porous carbon matrix;
[0098] The porous carbon precursor includes at least one of biomass and resin;
[0099] Activation treatment includes chemical activation or physical activation.
[0100] In the embodiment of the present application, a porous carbon matrix is obtained by activating a porous carbon precursor, which facilitates the accurate synthesis of a porous carbon matrix having a target pore volume and average pore size by controlling the activation conditions, thereby preparing a composite lithium supplement material with better effect.
[0101] A third aspect of the embodiments of the present application provides a positive electrode plate, comprising the above-mentioned composite lithium-replenishing material, or comprising the composite lithium-replenishing material obtained by the above-mentioned preparation method.
[0102] The positive electrode plate made of a composite lithium replenishing material provided in the embodiment of the present application shows a good lithium replenishing effect and is applied to a battery to help increase the positive electrode capacity.
[0103] In some embodiments, the positive electrode plate includes a current collector layer and an active material layer, the active material layer includes a composite lithium supplement material; the mass percentage of the composite lithium supplement material in the active material layer is 0.5% to 10%. In a specific example, the mass percentage of the composite lithium supplement material in the active material layer is 0.5%, 0.1%, 1.5%, 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, 5.0%, 6.0%, 7.0%, 8.0%, 9.0% or 10.0%, etc.
[0104] By adding an appropriate amount of composite lithium supplement material into the active material layer, it is beneficial to ensure that the battery obtains good electrochemical performance.
[0105] A fourth aspect of the present application provides a battery, comprising the above-mentioned positive electrode plate; or, comprising the above-mentioned composite lithium-supplementing material; or, comprising the composite lithium-supplementing material obtained by the above-mentioned preparation method.
[0106] The battery provided in the embodiments of the present application exhibits good electrochemical performance.
[0107] In some embodiments, the positive electrode plate contains a positive electrode active material, and the positive electrode active material includes at least one of a phosphate system; in a specific example, the positive electrode active material includes at least one of lithium iron phosphate, manganese phosphate, and lithium manganese iron phosphate.
[0108] In some embodiments, the battery further comprises a negative electrode plate, the negative electrode plate comprising a material capable of accepting and releasing lithium ions. In a specific example, the negative electrode plate comprises at least one of soft carbon, hard carbon, artificial graphite, natural graphite, silicon, silicon oxide, silicon-carbon composite, lithium titanate and a metal capable of forming an alloy with lithium.
[0109] In some embodiments, the battery includes an electrolyte.
[0110] Further, the electrolyte includes an electrolyte solvent, a lithium salt and some other functional additives. Among them, the electrolyte solvent is an ester solvent. Further, the ester solvent includes at least one of ethylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, polycarbonate, ethyl propionate and ethyl acetate. Further, the lithium salt includes LiPF6. Further, the additive includes fluoroethylene carbonate (FEC) and / or vinylene carbonate (VC).
[0111] A fifth aspect of an embodiment of the present application provides an electrical device comprising the above-mentioned battery.
[0112] In the embodiments of the present application, the electrical equipment provided includes but is not limited to automobiles, medical equipment, smart terminals, etc.
[0113] The present invention is described below with reference to specific examples. It should be noted that these examples are merely illustrative and do not limit the present invention in any way. The reagents used in the examples are all from Aladdin Biochemical Technology Co., Ltd.
[0114] Example 1
[0115] This embodiment provides a composite lithium supplement material, and the specific preparation method is as follows:
[0116] 50g of high-temperature carbonized coconut shell was placed in a test tube as a carbon source, and 50g of KOH activator was placed in the test tube and stirred evenly. The resulting mixture was placed in an argon atmosphere furnace and heated to 1000°C at a rate of 10°C / min, and then kept warm for 3h. After the insulation, the atmosphere furnace was naturally cooled to room temperature, and the porous carbon matrix was obtained after cleaning and drying. The pore volume of the porous carbon matrix was measured by a fully automatic specific surface and porosity analyzer to be 0.8cm 3 / g, and the average pore size is 20nm.
[0117] 20g of porous carbon matrix and 20g of lithium oxalate powder were placed in 50g of water and stirred thoroughly, and 200g of ethanol solution was slowly added during the stirring process (stirring speed: 1000rpm; solvent addition speed: 5ml / min). The obtained solution was spray-dried to obtain a composite of the carbon matrix and the lithium supplement active component as the composite lithium supplement material of the embodiment of the present application, wherein the mass fraction of the lithium supplement active component is 50%, that is, the mass percentage of the lithium supplement agent recorded in Table 1 is 50%.
[0118] The positive electrode sheet and lithium-ion secondary battery are prepared based on the above-mentioned composite lithium supplement material. The specific preparation method is as follows:
[0119] (1) Preparation of positive electrode sheet:
[0120] The active material lithium iron phosphate, the composite lithium supplement material, the conductive agent acetylene black, and the binder polyvinylidene fluoride (PVDF) are fully stirred and mixed in a solvent N-methylpyrrolidone at a weight ratio of 91:5:2:2, and then coated on the current collector Al foil for drying, rolling, and die-cutting to obtain the positive electrode sheet of the lithium ion secondary battery.
[0121] (2) Preparation of negative electrode sheet:
[0122] The silicon-carbon negative electrode material, the conductive agent acetylene black, the binder styrene-butadiene rubber (SBR), and the thickener sodium methyl cellulose (CMC) were fully stirred and mixed in a solvent deionized water according to a weight ratio of 95:2:2:1, and then coated on a current collector Cu foil for drying, rolling, and die-cutting to obtain a negative electrode sheet for a lithium-ion secondary battery.
[0123] (3) Preparation of electrolyte:
[0124] The electrolyte includes electrolyte solvent, lithium salt and some other functional additives. Among them, the electrolyte solvent is ethylene carbonate; 1M LiPF6 is dissolved in a non-aqueous organic solvent as a lithium salt, and fluoroethylene carbonate (FEC, 2%) and vinylene carbonate (VC, 2%) additives are added to the electrolyte.
[0125] (4) Preparation of lithium ion secondary batteries:
[0126] The positive electrode sheet obtained in step (1), the negative electrode sheet obtained in step (2), the electrolyte obtained in step (3) and the diaphragm obtained in step (4) are stacked, baked, injected, soaked, formed, aged, exhausted and divided to obtain a finished battery. In the formation process, the parameters are controlled as follows: charging at 0.05C for 2h at 45°C, switching to 0.2C constant current constant voltage to 3.8V (0.05C cut-off), and then charging at 0.02C constant current to 4.3V; the next step is to discharge at 1 / 3C cross current to 2V, and measure the initial battery discharge capacity.
[0127] Example 2
[0128] This embodiment provides a composite lithium supplement material, and the specific preparation method is as follows:
[0129] The preparation method of the composite lithium supplement material is as shown in Example 1, except that after adding KOH activator, the activation temperature is reduced from 1000°C to 800°C, and the pore volume of the porous carbon matrix is 0.4 cm 3 / g, and the average pore size is 20nm.
[0130] A positive electrode sheet and a lithium-ion secondary battery are prepared based on the above-mentioned composite lithium supplement material, and the specific preparation method is shown in Example 1.
[0131] Example 3
[0132] This embodiment provides a composite lithium supplement material, and the specific preparation method is as follows:
[0133] The preparation method of the composite lithium supplement material is as shown in Example 1, except that after adding KOH activator, the activation temperature is increased from 1000°C to 1200°C, and the pore volume of the porous carbon matrix is 1.2 cm 3 / g, and the average pore size is 20nm.
[0134] A positive electrode sheet and a lithium-ion secondary battery are prepared based on the above-mentioned composite lithium supplement material, and the specific preparation method is shown in Example 1.
[0135] Example 4
[0136] This embodiment provides a composite lithium supplement material, and the specific preparation method is as follows:
[0137] The preparation method of the composite lithium supplement material is as shown in Example 1, except that the mass of the added KOH activator is reduced from 50 g to 30 g, and the pore volume of the porous carbon matrix is 0.8 cm 3 / g, and the average pore size is 5nm.
[0138] A positive electrode sheet and a lithium-ion secondary battery are prepared based on the above-mentioned composite lithium supplement material, and the specific preparation method is shown in Example 1.
[0139] Example 5
[0140] This embodiment provides a composite lithium supplement material, and the specific preparation method is as follows:
[0141] The preparation method of the composite lithium supplement material is as shown in Example 1, except that the mass of the added KOH activator is increased from 50 g to 80 g, and the pore volume of the porous carbon matrix is 0.8 cm 3 / g, and the average pore size is 70nm.
[0142] A positive electrode sheet and a lithium-ion secondary battery are prepared based on the above-mentioned composite lithium supplement material, and the specific preparation method is shown in Example 1.
[0143] Example 6
[0144] This embodiment provides a composite lithium supplement material, and the specific preparation method is as follows:
[0145] The preparation method of the composite lithium supplement material is as shown in Example 1, except that phenolic resin is used to replace coconut shell, and lithium diquarate (Li2C4O4) is used to replace lithium oxalate (Li2C2O4).
[0146] Example 7
[0147] This embodiment provides a composite lithium supplement material, and the specific preparation method is as follows:
[0148] The preparation method of the composite lithium supplement material is as shown in Example 1, except that the mass of the added lithium oxalate is 4 g.
[0149] Example 8
[0150] This embodiment provides a composite lithium supplement material, and the specific preparation method is as follows:
[0151] The preparation method of the composite lithium supplement material is as shown in Example 1, except that the mass of the added lithium oxalate is 60 g.
[0152] Example 9
[0153] This embodiment provides a composite lithium supplement material, and the specific preparation method is as follows:
[0154] The preparation method of the composite lithium supplement material is as shown in Example 1, except that the mass of the added lithium oxalate is 100 g.
[0155] Example 10
[0156] This embodiment provides a composite lithium supplement material, and the specific preparation method is as follows:
[0157] The preparation method of the composite lithium supplement material is as shown in Example 1, except that the addition rate of ethanol is 0.5 ml / min.
[0158] Embodiment 11
[0159] This embodiment provides a composite lithium supplement material, and the specific preparation method is as follows:
[0160] The preparation method of the composite lithium supplement material is as shown in Example 1, except that the addition rate of ethanol is 20 ml / min.
[0161] Example 12
[0162] This embodiment provides a composite lithium supplement material, and the specific preparation method is as follows:
[0163] The preparation method of the composite lithium supplement material is as shown in Example 1, except that the stirring speed is 100 rpm.
[0164] Example 13
[0165] This embodiment provides a composite lithium supplement material, and the specific preparation method is as follows:
[0166] The preparation method of the composite lithium supplement material is as shown in Example 1, except that the stirring speed is 5000 rpm.
[0167] Comparative Example 1
[0168] This case provides a composite lithium supplement material, and the specific preparation method is as follows:
[0169] The preparation method of the composite lithium supplement material is as shown in Example 1, except that the mass of the KOH activator is reduced from 50 g to 15 g, and the pore volume of the porous carbon matrix is 0.8 cm 3 / g, and the average pore size is 2nm.
[0170] A positive electrode sheet and a lithium-ion secondary battery are prepared based on the above-mentioned composite lithium supplement material, and the specific preparation method is shown in Example 1.
[0171] Comparative Example 2
[0172] This case provides a composite lithium supplement material, and the specific preparation method is as follows:
[0173] The preparation method of the composite lithium supplement material is as shown in Example 1, except that the mass of the KOH activator is increased from 50 g to 110 g, and the pore volume of the porous carbon matrix is 0.8 cm 3 / g, and the average pore size is 100nm.
[0174] A positive electrode sheet and a lithium-ion secondary battery are prepared based on the above-mentioned composite lithium supplement material, and the specific preparation method is shown in Example 1.
[0175] Comparative Example 3
[0176] This case provides a composite lithium supplement material, and the specific preparation method is as follows:
[0177] The preparation method of the composite lithium supplement material is as shown in Example 1, except that after adding KOH activator, the activation temperature is reduced from 1000°C to 600°C, and the pore volume of the porous carbon matrix is 0.3 cm 3 / g, and the average pore size is 20nm.
[0178] A positive electrode sheet and a lithium-ion secondary battery are prepared based on the above-mentioned composite lithium supplement material, and the specific preparation method is shown in Example 1.
[0179] Comparative Example 4
[0180] This case provides a composite lithium supplement material, and the specific preparation method is as follows:
[0181] The preparation method of the composite lithium supplement material is as shown in Example 1, except that after adding KOH activator, the activation temperature is increased from 1000°C to 1300°C, and the pore volume of the porous carbon matrix is 1.5 cm 3 / g, and the average pore size is 20nm.
[0182] A positive electrode sheet and a lithium-ion secondary battery are prepared based on the above-mentioned composite lithium supplement material, and the specific preparation method is shown in Example 1.
[0183] Performance Testing
[0184] 1. Test method:
[0185] (1) Morphological characterization of composite lithium supplement materials: Scanning electron microscopy (SEM) was used for characterization.
[0186] (2) Conductivity test of composite lithium supplement material powder: refer to GB / T 30835-2014.
[0187] (3) Test of the positive electrode capacity in grams of lithium-ion secondary batteries: The actual capacity of the battery is recorded as x, and the total active mass of LFP inside the battery is recorded as y. The positive electrode capacity in grams of the battery is defined as z = x / y (unit: mAh / g). The larger the value of z, the more active lithium is released by the decomposition of the composite lithium supplement material, and the higher the decomposition efficiency.
[0188] Table 1 Performance test results of samples provided by Examples 1-5 and Comparative Examples 1-4
[0189]
[0190] Note: In Table 1, “Pore volume (cm3 / g) / pore diameter (nm) of porous carbon matrix” means two parameters: “Pore volume (cm3 / g) of porous carbon matrix” and “Pore diameter (nm) of porous carbon matrix”, not a ratio relationship.
[0191] 2. Test result description:
[0192] (1) Morphological characterization of composite lithium supplement materials Figure 1-Figure 4 As shown, Figure 1-Figure 2 This is the case where the lithium supplement agent deposition is good. In this case, the lithium supplement agent is completely deposited into the internal pores of the porous carbon. The sample conductivity under this condition is high, which is more conducive to the later classification. On the contrary, Figure 3-Figure 4 This is a case where the lithium supplement agent has poor deposition. In this case, part of the lithium supplement agent grows onto the surface of the carbon matrix, which will cause the lithium supplement agent to agglomerate, reduce conductivity, and make it difficult to decompose in the later stage. The pore size distribution of the porous carbon matrix, the internal pore volume, and the actual deposition amount of the lithium supplement agent will all have a significant impact on the deposition quality of the lithium supplement agent.
[0193] (2) The test results of the electrical conductivity of the composite lithium supplement material are shown in Table 1. The electrical conductivity of the composite lithium supplement material is related to the pore volume distribution of the porous carbon matrix and the deposition position of the lithium supplement active component. For the porous carbon matrix, a higher pore volume means that there are a large number of pores inside the particles, which will lead to a reduction in the electron transmission pathway, and then lead to a decrease in the electrical conductivity of the composite lithium supplement material; in addition, the deposition position of the lithium supplement active component will also affect the electrical conductivity of the composite lithium supplement material. If the lithium supplement active component is deposited in the pores of the porous carbon matrix, the electron conduction circuit will not be greatly affected, and the electrical conductivity will not decrease significantly; if the lithium supplement active component is not deposited in the pores of the porous carbon matrix, but is deposited on the surface of the particles, due to the low electrical conductivity of the lithium supplement active component, the electrical conductivity of the composite lithium supplement material will decrease.
[0194] From the perspective of lowering the decomposition potential, the ideal structure is to deposit the lithium-replenishing active components into the pores of the porous carbon matrix. At this time, the lithium-replenishing active components with low electrical conductivity are surrounded by the porous carbon matrix, forming a good conductive network, which is beneficial to lowering the decomposition voltage.
[0195] (3) The test results of the positive electrode capacity of the composite lithium supplement material are shown in Table 1. Comparing the test data of the embodiment and the comparative example, the porous carbon matrix and pore volume have a significant effect on the conductivity and positive electrode capacity of the composite lithium supplement material. 3 / g~1.2cm 3 / g, the powder conductivity and positive electrode gram capacity of the composite lithium supplement material corresponding to the porous carbon matrix with an average pore size of 5nm to 70nm have significant advantages; furthermore, 0.8cm 3 The composite lithium-supplementing material corresponding to the porous carbon matrix with a pore volume of 0.14 W / g and an average pore size of 20 nm has the highest electrical conductivity and positive electrode capacity, indicating that the corresponding composite lithium-supplementing material is most completely decomposed (as shown in Example 1).
[0196] In summary, the pore size and pore volume of the porous carbon matrix have a great influence on the deposition of the active components of lithium replenishment. From the perspective of average pore size, the use of a porous carbon matrix with an appropriate average pore size, on the one hand, is conducive to giving full play to the confinement effect of the pore size, synthesizing a composite lithium replenishment material with a smaller crystal size, and reducing the decomposition voltage; on the other hand, it ensures that the active components of lithium replenishment are fully diffused into the pores of the porous carbon matrix in the form of ions, and ensures that the active components of lithium replenishment are recrystallized and deposited in the pores, rather than on the surface of the porous carbon matrix, thereby helping to improve the utilization rate, conductivity and positive electrode gram capacity of the composite lithium replenishment material.
[0197] From the perspective of pore volume, using a porous carbon matrix with an appropriately sized pore volume can, on the one hand, help reduce the damage to the conductive pathway inside the porous carbon matrix and improve the conductivity; on the other hand, it can help ensure that the composite lithium-replenishing active components are recrystallized and deposited inside the pores as much as possible rather than on the surface, thereby improving the decomposition efficiency and utilization rate of the lithium-replenishing active components.
[0198] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A composite lithium supplement material, characterized in that: include: A porous carbon substrate, and an organic lithium compound distributed at least in the pores of the porous carbon substrate; The pore volume of the porous carbon matrix is 0.4 cm 3 / g~1.2cm 3 / g, and the average pore size of the porous carbon matrix is 5nm-70nm.
2. The composite lithium supplement material according to claim 1, characterized in that: The porous carbon matrix includes at least one of graphite, soft carbon and hard carbon; And / or, the organic lithium compound includes at least one of Li2C4O4, Li2C2O4, Li2C3O5, Li2C5O5, Li2C4O6 and Li2C6O6.
3. The composite lithium supplement material according to claim 1 or 2, characterized in that: The mass ratio of the porous carbon matrix to the organic lithium compound is 5:1 to 1:
5.
4. The composite lithium supplement material according to any one of claims 1 to 3, characterized in that: The crystal grain size of the organic lithium compound is 1 nm to 20 nm.
5. A method for preparing a composite lithium supplement material, characterized in that: include: distributing an organic lithium compound in the pores of a porous carbon matrix to obtain a composite lithium supplement material; In the composite lithium supplement material, the pore volume of the porous carbon matrix is 0.4 cm 3 / g~1.2cm 3 / g, and the average pore size of the porous carbon matrix is 5nm-70nm.
6. The preparation method according to claim 5, characterized in that: The method of distributing the organic lithium compound in the pores of the porous carbon matrix includes a recrystallization method.
7. The method for preparing the composite lithium supplement material according to claim 6, characterized in that: The recrystallization method comprises the steps of: adding the porous carbon matrix and the organic lithium compound into a first solvent to obtain a mixed solution; adding a second solvent to the mixed solution for recrystallization; The first solvent and the second solvent are removed to obtain a composite lithium supplement material; the solubility of the organic lithium compound in the second solvent is lower than that in the first solvent.
8. The method for preparing the composite lithium supplement material according to claim 7, characterized in that: Each raw material satisfies at least one of the following (1) to (4): (1) The porous carbon matrix includes at least one of graphite, soft carbon and hard carbon; (2) The organic lithium compound includes at least one of Li2C4O4, Li2C2O4, Li2C3O5, Li2C5O5, Li2C4O6 and Li2C6O6; (3) The first solvent includes water; (4) The second solvent includes ethanol.
9. The method for preparing the composite lithium supplement material according to claim 7 or 8, characterized in that: In the step of adding a second solvent to the mixed solution for recrystallization, the control parameters include: The stirring speed is: 100 rpm to 5000 rpm; and / or, the adding speed of the second solvent is 0.5 ml / min to 20 ml / min.
10. The method for preparing the composite lithium supplement material according to any one of claims 5 to 9, characterized in that: The method also includes the steps of preparing the porous carbon matrix: subjecting a porous carbon precursor to an activation treatment to obtain the porous carbon matrix; The porous carbon precursor includes at least one of biomass and resin; The activation treatment includes chemical activation or physical activation.
11. A positive electrode sheet, characterized in that: The composite lithium supplement material comprises any one of claims 1 to 4, or the composite lithium supplement material obtained by the preparation method of any one of claims 5 to 10.
12. The positive electrode sheet according to claim 11, characterized in that: It comprises a current collector layer and an active material layer, wherein the active material layer contains the composite lithium supplement material; the mass percentage of the composite lithium supplement material in the active material layer is 0.5% to 10%.
13. A battery, characterized in that: Contains the positive electrode sheet according to claim 9 or 10; or, contains the composite lithium supplement material according to any one of claims 1 to 4; or, contains the composite lithium supplement material obtained by the preparation method according to any one of claims 5 to 10.
14. An electrical device, characterized in that: A battery comprising the battery of claim 11.
Citation Information
Patent Citations
Positive electrode lithium supplement additive and preparation method thereof
CN112713275A
Porous carbon material for lithium battery negative electrode and preparation method of porous carbon material
CN115692691A
Positive lithium supplementing pole piece, preparation method thereof and lithium ion battery
CN115939391A
Composite lithium supplementing material and preparation method thereof, positive pole piece, battery and power utilization device
CN117174884A
Positive electrode lithium supplement agent and preparation method thereof, positive electrode and lithium ion battery
CN118231801A